Political Development: Structuring the Administration of Local Government - Muhammad Nasir (International Journal of Qualitative Research, 2022)
Local Government Administration Arrangement Is part of Political Development in Aoma Village, Wolasi District, South Konawe Regency, The purpose of the study is to find out the arrangement of government administration in supporting the service This location selection is based on the consideration that the implementation of government administrative services needs to be arranged optimally for service improvement. Used qualitative descriptive research where data collection is carried out in natural conditions (natural setting), primary data sources and data collection techniques are more in-depth interviews and documentation. Data analysis of categorization, reduction, and interpretation. The results of the study showed the arrangement of the implementation of government administration in Aoma Village, Wolasi District, South Konawe Regency in the form of government by providing services to the community in the form of population administration activities, carrying out data collection and inventory of village assets.